2021
DOI: 10.22201/cgeo.20072902e.2021.2.1645
|View full text |Cite
|
Sign up to set email alerts
|

Las Cabras volcano, Michoacán-Guanajuato Volcanic Field, México: Topographic, climatic, and shallow magmatic controls on scoria cone eruptions

Abstract: Scoria cones are abundant in most volcanic fields on Earth, such as the Michoacán-Guanajuato Volcanic Field, in the central-western sector of the Trans-Mexican Volcanic Belt. However, there are few in-depth studies on their eruptive style and controlling factors, despite of their diversity in shape and composition which implies a wide range of hazards. Here, we present results of morphologic, stratigraphic, sedimentary, petrographic, and geochemical studies of the prominent Las Cabras scoria cone located west … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…were reported from Cueva de los Hacheros (Punzo-Díaz and Martínez-Vázquez 2018, 2021) at the southern limit of the MGVF (Figure 2). Recent radiometric dating efforts in the MGVF (e.g., Chevrel et al 2016a; Guilbaud et al 2012, 2021; Kshirsagar et al 2015, 2016; Mahgoub et al 2017; Osorio-Ocampo et al 2018; Pola et al 2014; Ramírez-Uribe et al 2019; Reyes Guzmán et al 2018) have revealed numerous Late Pleistocene/Holocene monogenetic eruptions, and it seems safe to say that the average time interval between them is <400 years. Many of these must have affected ancient population groups since the first arrival of early man in this part of the American continent, although evidence for the direct impact of eruptions on early pre-Hispanic dwellers remains sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were reported from Cueva de los Hacheros (Punzo-Díaz and Martínez-Vázquez 2018, 2021) at the southern limit of the MGVF (Figure 2). Recent radiometric dating efforts in the MGVF (e.g., Chevrel et al 2016a; Guilbaud et al 2012, 2021; Kshirsagar et al 2015, 2016; Mahgoub et al 2017; Osorio-Ocampo et al 2018; Pola et al 2014; Ramírez-Uribe et al 2019; Reyes Guzmán et al 2018) have revealed numerous Late Pleistocene/Holocene monogenetic eruptions, and it seems safe to say that the average time interval between them is <400 years. Many of these must have affected ancient population groups since the first arrival of early man in this part of the American continent, although evidence for the direct impact of eruptions on early pre-Hispanic dwellers remains sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Geological map of the Zacapu lacustrine basin (color-coded according to ages), modified after Guilbaud et al 2021. Black quadrangles delimit the areas previously studied in detail: Western quadrangle (shown in Figure 4) originally mapped by Reyes-Guzmán et al (2018); southern quadrangle by Ramírez-Uribe et al (2019); eastern quadrangle by Kshirsagar et al (2015); and northern quadrangle by Kshirsagar et al (2016).…”
Section: Geological Contextmentioning
confidence: 99%